Strategi Pengelolaan Lingkungan di Bentanglahan Solusional, Fluvio-marine, dan Marine Menggunakan Analisis SWOT di Kabupaten Badung - Khaerul Amru; Nur Laksmita, Aulia; Mutia Herni Ningrum; Said Fahmi; Erwika Dhora Jati (BRIN Publishing (Penerbit BRIN), 2024)
Badung Regency has a variety of landscape structures formed from various abiotic components that are integrated between climate, topography, and interactions between organisms to create specific spatial patterns. This study aims to identify problems and develop environmental management strategies in solutional landforms (Jimbaran Village), fluvio-marine (Tahura Ngurah Rai), and marine (Kuta Beach). The method used in this study is to use SWOT analysis with weighting and descriptive-analytical. Based on the results of identifying ecological problems in solutional areas are water drought and poor waste management. Environmental problems in fluvio-marine landscapes are related to waste. Environmental problems in marine landforms in Kuta Beach are the difficulty of clean water and drinking water sources, the potential for tsunami disasters, garbage as an active source of pollutants, and road congestion along Kuta Beach. Meanwhile, the management strategy from the results of the analysis obtained six points, namely the development of various types of fish pond farming, providing a means of marketing fish products, supporting the local economy by purchasing local farmers' fish products, improving environmental supervision of business people on waste management, restrictions on tourist activities in the buffer zone, and plant types that can support the sustainability of water resources and improve the function of buffer zones. Abstrak Kabupaten Badung memiliki beragam struktur bentanglahan yang terbentuk dari berbagai komponen abiotik yang terintegrasi antara iklim, topografi, dan interaksi antar organismenya sehingga membentuk pola spasial yang spesifik. Penelitian ini bertujuan untuk mengidentifikasi permasalahan lingkungan yang timbul pada bentanglahan solusional (Desa Jimbaran), fluvio-marine (Tahura Ngurah Rai), dan marine (Pantai Kuta). Metode yang digunakan dalam penelitian ini adalah analisis SWOT dengan pembobotan dan deskriptif-analitis. Berdasarkan hasil identifikasi permasalahan lingkungan di daerah solusional adalah kekeringan air dan pengelolaan limbah yang buruk. Masalah lingkungan di bentanglahan fluvio-marine terkait dengan limbah. Masalah lingkungan pada bentanglahan marine di Pantai Kuta adalah sulitnya sumber air bersih dan air minum, potensi bencana tsunami, sampah sebagai sumber polutan aktif, dan kemacetan jalan di sepanjang Pantai Kuta. Sementara itu, strategi pengelolaan dari hasil analisis diperoleh enam poin, yaitu pengembangan berbagai jenis budidaya tambak ikan, menyediakan sarana pemasaran produk ikan, mendukung ekonomi lokal dengan membeli produk ikan petani lokal, meningkatkan pengawasan lingkungan pelaku bisnis terhadap pengelolaan limbah, pembatasan kegiatan wisata di zona penyangga, dan jenis tanaman yang dapat mendukung keberlanjutan sumber daya air dan meningkatkan fungsi zona penyangga.